The correlation of clinical status and imaging findings in patients with chronic low back pain: Clinical and imaging findings in low back pain - Kırdar, Nurten Nas; Bayram, Korhan Barış (Journal of Surgery and Medicine, 2022)
Background/Aim: Chronic low back pain (LBP) is a common health problem that negatively affects quality of life. A multidisciplinary approach is recommended in treating chronic LBP. In the literature, we could not find any study examining the relationship between clinical status, activities of daily living, angular measurements in the lumbar region, and spondylosis level in patients with LBP. We aimed to reveal whether there is a relationship between the severity of the clinical condition and these angular measurements. In addition, there are opposing views in the literature about the relationship between obesity and LBP, and we planned to investigate this issue in our study. We aimed to investigate the correlation between clinical, functional evaluations, and radiographic findings in patients with chronic LBP and examine the relationship between these variables and gender and educational level. We also determine the effects of age, body mass index (BMI), and waist circumference on these variables. Methods: The research was designed as a cross-sectional, uncontrolled study. Seventy patients aged 18–65 years with chronic LBP and VAS (Visual Analog Scale) values ≥ 3 were included. Patients were grouped by gender and educational level. Lumbar lordosis angle (LLA), sacral inclination angle (SIA), and Kellgren-Lawrence (K-L) grade were recorded. VAS, Oswestry Disability Index (ODI), Back Pain Functional Scale (BPFS), and Katz Activities of Daily Living (Katz-ADL) scores were calculated. Pearson correlation analysis determined the normal distribution status of the variables. Spearman’s correlation analysis evaluated the linear relationship between ODI and BPFS and LLA and SIA continuous variables. A p-value of < 0.05 was considered statistically significant. Results: A total of 70 patients (47 females and 23 males) with chronic LBP were included in the study. Mean BMI (28.2 [6.1] kg/m2) and waist circumference (95.7 [12.7] cm) of the patients were above normal ranges (normal BMI: 18.5–24.99 kg/m², normal waist circumference: < 80 cm for women, < 90 cm for men). Katz-ADL (P = 0.006) and BPFS scores (P = 0.027) were lower, and LLA (P = 0.042) was higher in women than men. The BPFS score was lower in the low-level education group than in the high-level education group (P = 0.004). There was a positive correlation between age and SIA (P = 0.028, r = 0.262), and between age and K-L grade (P < 0.001, r = 0.633). A positive correlation was also observed between BMI and K-L grade (P = 0.001, r = 0.395) and waist circumference and K-L grade (P < 0.001, r = 0.442). Conclusion: No correlation was found between functional clinical scales and radiographic findings in patients with chronic LBP. Increasing age, BMI, and waist circumference were associated with more severe radiographic osteoarthritis of the lumbar spine, whereas female gender and low educational level were related to lower functional levels. Further extensive studies, including a larger number of patients, are needed to clarify our results.